2015
DOI: 10.1371/journal.pone.0129927
|View full text |Cite
|
Sign up to set email alerts
|

Similar Occurrence of Febrile Episodes Reported in Non-Atopic Children at Three to Five Years of Age after Prebiotics Supplemented Infant Formula

Abstract: This is a follow up study of a multicenter randomised placebo-controlled trial in seven centres in five West European countries. The RCT assessed the effect of infant formula supplemented with a mixture of prebiotics (with neutral short-chain and long-chain oligosaccharides and pectin-derived acidic oligosaccharides) during infancy in term-born children (n=1130). In the follow-up study 672 children (60% of the study population) participated: 232 (56%) from the prebiotics group (PG), 243 (58%) from the control … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…No differences between groups were found in a studies comparing GOS- (10) (no data shown), GOS/FOS-and AOS-(0•8 g/100 ml) supplemented formulae with unsupplemented formula (P > 0•05) (24) . There were also no differences in either the duration of vomiting (median 2 in the supplemented formula group compared with the unsupplemented formula group (31) .…”
Section: Clinical Effectsmentioning
confidence: 84%
See 2 more Smart Citations
“…No differences between groups were found in a studies comparing GOS- (10) (no data shown), GOS/FOS-and AOS-(0•8 g/100 ml) supplemented formulae with unsupplemented formula (P > 0•05) (24) . There were also no differences in either the duration of vomiting (median 2 in the supplemented formula group compared with the unsupplemented formula group (31) .…”
Section: Clinical Effectsmentioning
confidence: 84%
“…Among new studies identified, there were three studies that were not included in the previous Committee systematic review despite having been published before the review (10,16,18) . A number of RCT described the same study population but reported different outcome measures (6,7,11,24,26,30,31,(34)(35)(36)(37)(38)(39)(40)(41)(42) . The online Supplementary Table S2 summarises the characteristics of the excluded trials, with reasons for exclusion.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is known that a healthy microbiota can protect against pathogens, a phenomenon referred to as colonization resistance . The very low number of bacterial infections in Dutch infants in general may have attributed to the absence of an association …”
Section: Discussionmentioning
confidence: 99%
“…28 The very low number of bacterial infections in Dutch infants in general may have attributed to the absence of an association. 29 An important strength of this study is the prospective data collection in a relatively large group of healthy, term-born infants.…”
Section: Discussionmentioning
confidence: 99%